ASSESSMENT OF FUELWOOD HARVESTING AND ITS IMPLICATION ON VEGETATION LOSS IN OFU LOCAL GOVERNMENT AREA, KOGI STATE, NIGERIA: None - Iyeh, Omachi Pius; Jenkwe, E. D. (FUDMA JOURNAL OF SCIENCES, 2020)
ABSTRACTThe economic drive of the people in exploiting forests resources to earn income has in different ways impacted the natural environments of Kogi State leading to vegetation loss and environmental degradation. The study assessed fuelwood harvesting and its implication on vegetation loss in Ofu Local Government Area of Kogi State from 1989 to 2019. The objectives of the study are to; map out deforested areas and ascertain the rate of deforestation between 1989-2019 using Landsat images, identify the relationship between fuelwood consumption and vegetation loss in the area, and determine the pattern of land use/land cover change between 1989-2019 in the study area. Primary and Secondary Data were used. Landsat images of 1989, 1999, 2009 and 2019 obtained from the United State Geological Survey (USGS) with Medium resolution. The result show that the cumulative value of total vegetation lost with decrease of -78 sq km from 1989-1999 which decreases to -145sq km from 1999-2009 and similarly decreases to -508 sq km from 2009-2019 shows that the study area vegetation cover lost is 47.8% spread throughout the three decades. Thus, the total area is 1,680km2 compared to the -430 Km2 of the total vegetation lost. In all, the NDVI result shows a drastic reduction by 0.1647 from 1 to 0.0676 for the periods of three decades. The study suggested that; Government should try to stabilize the provision of other alternative sources of energy (electricity, fossil fuels and coal) at an affordable price, which will encourage people to stop using fuelwood.